High resolution upper crustal velocity and seismogenic structure of the Huoshan “seismic window” in the Dabie orogenic belt - Li, Lingli; Yao, Huajian; Zhang, Bing; Li, Junhui; Shu, Peng; Yang, Yuanyuan; Wang, Xiaoli; Zhou, Dongrui; Zhao, Peng; Luo, Jiaji (Frontiers in Earth Science, 2023)
Huoshan “seismic window” is located in the northern margin of the Dabie Orogen belt, the contact zone between North China and the Yangtze plate, where the seismic activity is mainly concentrated in this area. Small earthquake swarms in this region often appear before significant moderate-strong earthquakes in East China. To reveal the fine structures of several faults and discuss their correlation with the seismic activity, a seismic array composed of 136 sets of short period seismometers was deployed in the Huoshan region and its surrounding areas. Ambient noise data were recorded for 1 month, and a 3-D velocity structure model of the upper crust was constructed. The results show that with the Meishan-Longhekou and Qingshan-Xiaotian faults as the boundary, the Dabie Mountain, Hefei Basin, North Dabie and North Huaiyang show exhibit obvious high and low velocity variation characteristics. The shallow crust along the NW-trending, normal Qingshan-Xiaotian fault, presents a high velocity zonal distribution, which is related to the large number of magmatic and metamorphic rocks exposed under the strong metamorphic power in this region. The NE-trending Tudiling-Luoerling fault comprised three groups of parallel and nearly vertical en echelon secondary faults in the upper crust, which control most of the seismic activities. A relatively low velocity anomaly is observed in the seismic concentrated occurrence layer near the intersection of the fault. It suggests that this area inherits the property of the low velocity detachment zone of the middle crust in the wing of the Dabie Mountain dome structure, and a relatively broken weak structural zone form near the intersection of the fault, which leads to the release of small strain accumulation, thus enriching small earthquake activities. The focal depth of earthquakes above ML3 mainly distribute along the Tudiling-Luoerling fault plane, which is indicated this fault is the main seismogenic fault of greater seismicity in Huoshan “seismic window”. This study provides an important model basis for reliable earthquake location, focal mechanism and the determination of possible earthquake risk sites, and provides a reference for the further study of small earthquake activity mechanism of other "seismic windows" in China.